Human Capital for a Modern Society : General Education in the Maldives - World Bank (Washington, DC, 2017)
The Republic of Maldives, a multi-island nation of spectacular natural beauty, is one of the most advanced economies in South Asia. The Maldives consists of an archipelago of nearly 1,200 islands and a population of about 374,000 inhabitants: 300,000 Maldivians and 74,000 expatriate workers. The Maldives had attained a gross national income (GNI) per capita of US$5,790 in 2010. The country ranked 109'th in the human development index (HDI) for 2011, which is the second highest HDI rank in South Asia after Sri Lanka. The Maldives is seeking to accelerate human development and promote economic prosperity. The development of human capital is central to the country's strategy to achieve this goal. The present study analyzes the main challenges facing the general education sector and presents, for the consideration of policy makers in the country, a set of strategic options for the future development of general education.